Evaluating Spatiotemporal Enrichment and Contamination of Heavy Metals in the Surface Water of Qua Iboe River, Niger Delta, Nigeria - Udeme Effiong Jonah (Zanco Journal of Pure and Applied Sciences)
The present study deals with spatial and temporal variation of heavy metals and its contaminant in Qua Iboe River within five sampling locations, from January 2020 to June 2021. Seven heavy metals (Cd, Zn, Pb, Fe, Mn, Cr and Ni) were investigated using standards methods. Contamination factor (Cf), degree of contamination (DC), ecological risk factor (Er) and potential ecological risk index (PERI) were used to determined the contamination status and ecological risk. The spatial mean values of  Zn, Pb, Fe and Ni in all the locations, Cd in locations 2, 3, 5; Cd mean value in wet season and the mean value of Zn, Pb, Fe , Ni in both seasons were exceeded the limits. The Cf value for Cd (location 1), Cr (locations 1, 2, 4, 5) and in both seasons were less than 1, DC values across the locations and in both seasons were ≥ 24 (very high degree of contamination), ER values for Zn in locations 1, 4 and 5 were between 40 ≤ – < 80 (moderate), 2 was between 160 ≤ – < 320 (high), location 3 and  in both seasons were between 80 ≤ – < 160 (considerable high ecological  risk). The PERI values in locations 2, 3, 5 and for the seasons were ranged between 150 < PERI < 300 indicating moderate ecological risk. These were influenced by human activities, geogenic and seasons. Frequent monitoring is recommended to salvage the aquatic ecosystem and the inhabitant biota.